Generic skills for the workplace : A study of graduating students at UiTM Sarawak / Prof. Madya Pauline Achan ... [et al.] - Achan, Pauline; Philip, Bromeley; Nee Gaik, Mary Gunjey (2006)
This research was undertaken to firstly determine the extent to which Universiti Teknologi MARA (UiTM) Sarawak's graduating students are prepared in terms of the four types of employability skills. Secondly, to determine the extent to which these skills are teachable. Thirdly, to gauge the lecturers' perception of the students' preparedness in relation to the skills and lastly, to determine whether the skills identified match with the employer's/the industry's needs and requirements. The research involved 334 UiTM Sarawak's graduating students in semester July to November 2005; 13 employers experienced in supervising students who had undergone practical training with them; and 34 lecturers